2017
DOI: 10.1093/neuros/nyx195
|View full text |Cite
|
Sign up to set email alerts
|

Granger Causality Analysis of Interictal iEEG Predicts Seizure Focus and Ultimate Resection

Abstract: BACKGROUNDA critical conceptual step in epilepsy surgery is to locate the causal region of seizures. In practice, the causal region may be inferred from the set of electrodes showing early ictal activity. There would be advantages in deriving information about causal regions from interictal data as well. We applied Granger's statistical approach to baseline interictal data to calculate causal interactions. We hypothesized that maps of the Granger causality network (or GC maps) from interictal data might inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 25 publications
1
63
0
Order By: Relevance
“…We chose our biomarkers with two criteria in mind: 1) to be exhaustive regarding the different types of measures used (i.e. univariate, bivariate and multivariate); 2) biomarkers should have been reported to show an overall significant effect in discriminating between healthy and pathological tissue using inter-ictal intracranial recordings [23][24][25][27][28][29][31][32][33][34][35]60 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We chose our biomarkers with two criteria in mind: 1) to be exhaustive regarding the different types of measures used (i.e. univariate, bivariate and multivariate); 2) biomarkers should have been reported to show an overall significant effect in discriminating between healthy and pathological tissue using inter-ictal intracranial recordings [23][24][25][27][28][29][31][32][33][34][35]60 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be generalized to a multivariate scenario where the reduction of modelling error of the multivariate model is used instead (see Blinowska 53 for detailed review). Park and colleagues 29 successfully applied time based multivariate Granger causality to inter-ictal ECoG recordings showing that ictal networks can be inferred from inter-ictal recordings. They showed that there was a significant correlation between the epileptogenic location inferred using ictal recordings (i.e.…”
Section: Granger Causality (Time-domain)mentioning
confidence: 99%
See 2 more Smart Citations
“…Network measures characterizing individual nodes try to describe the importance of a node to the whole network. In different types of networks it has been found that nodes in the SOZ/RA are often more influential compared to non-SOZ/RA nodes in the sense that on average the degree, net outflow, and centrality of SOZ/RA nodes is elevated [38,105,107,[178][179][180][181]. However, it has not been investigated how network analysis can be used to plan the extent of the resection, which might be one of the reasons that it is not used in standard clinical practice [84].…”
Section: Network Models For Epilepsy Surgerymentioning
confidence: 99%